2020
DOI: 10.3390/polym12051164
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Influence of the Sourcing Voltage on Polyaniline Composites for Stress Sensing Applications

Abstract: Polyaniline (PANI) has recently gained great attention due to its outstanding electrical properties and ease of processability; these characteristics make it ideal for the manufacturing of polymer blends. In this study, the processing and piezoresistive characterization of polymer composites resulting from the blend of PANI with ultra-high molecular weight polyethylene (UHMWPE) in different weight percentages (wt %) is reported. The PANI/UHMWPE composites were uniformly homogenized by mechanical mixing and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 81 publications
1
6
0
Order By: Relevance
“…As shown in previous work, carbon nanotubes and conductive polymers exhibit a nonlinear current voltage characteristic [33,34]. In this study, under the measuring conditions used, no clear nonlinearity was found in the results.…”
Section: Gauge Factor Evaluationsupporting
confidence: 73%
“…As shown in previous work, carbon nanotubes and conductive polymers exhibit a nonlinear current voltage characteristic [33,34]. In this study, under the measuring conditions used, no clear nonlinearity was found in the results.…”
Section: Gauge Factor Evaluationsupporting
confidence: 73%
“…Thus, various salts have been incorporated into different host polymer matrices [ 8 , 9 , 10 , 11 ]. Polymer electrolytes are hosts for ion carriers while conductive polymers such as polyaniline (PANI) are hosts for electron carriers [ 12 ]. Polymer electrolyte ions are responsible for conduction [ 9 , 10 , 11 ], while in PANI electrons are sources for conduction [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer electrolytes are hosts for ion carriers while conductive polymers such as polyaniline (PANI) are hosts for electron carriers [ 12 ]. Polymer electrolyte ions are responsible for conduction [ 9 , 10 , 11 ], while in PANI electrons are sources for conduction [ 12 ]. Polymers used for polymer electrolyte preparation can be categorized into natural polymers and synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations